APPLICATION OF PLACKETT-BURMAN AND BOX-BEHNKEN DESIGNS FOR SCREENING AND OPTIMIZATION OF ROTIGOTINE HCL AND RASAGILINE MESYLATE TRANSFERSOMES: A STATISTICAL APPROACH - PATEL, SHIVANI; JHA, LALIT LATA (International Journal of Applied Pharmaceutics, 2023)
Objective: The objective of this study was to optimize the transferosomal formulation containing Rotigotine HCL(RTG) and Rasagiline mesylate (RSM) and to identify the significant factors affecting particle size and entrapment efficiency. Methods: The optimized batch was characterized using various techniques, such as TEM to confirm the shape of vesicles and FTIR analysis to check the compatibility of the formulation. The vesicle size of the transferosomes was determined using a zeta sizer. The entrapment efficiency of both drugs was also determined. In vitro drug permeation investigation was carried out from the optimized batch to determine the cumulative permeation rate after 24 h. The study also evaluated the deformability index of the transferosomes. Results: The results showed that transferosomes were spherical particles with a uniform distribution and suitable for drug delivery. The vesicle size of the transferosomes was in the range of 54.05-167.98 nm and 66.02-184.04 nm for RTG and RSM transferosomes, respectively. The polydispersity index for RTG transferosomes was observed in the range of 0.242-0.508, the entrapment efficiency of RTG was 45.66-88.96% and RSM was found to be 57.6-92.57%. The in vitro drug permeation investigation from the optimized batch showed a cumulative permeation rate of 92.268% of RTG and 87.72% of RSM after 24 h. Conclusion: The study findings suggest that transferosomes can be a promising drug delivery system for rotigotine HCL and rasagiline mesylate. The optimized batch showed high entrapment efficiency, good permeation rate, and optimal deformability, making it a suitable option for drug delivery.